Modelling the thermal radiation from kitchen hob fires. (July 2020) - Spearpoint, Michael; Hopkin, Charlie; Hopkin, Danny
Kitchen hob fires present a potential threat to occupants escaping from dwellings and calculations may be needed to assess the hazard. Determination of the thermal heat flux from flames to a target can be achieved through the use of hand calculation methods or computational tools. This article compares point source, parallel plane and cylindrical view factor hand calculations and computational simulations using B-RISK and Fire Dynamics Simulator of thermal heat flux with kitchen hob fire experiments presented in the literature. Knowing the level of accuracy of each method provides useful information to designers. Although the point source model is influenced by whether the radial distance is measured perpendicular to the heat flux target or is offset relative to the centre of the flame, the article concludes that it provides an adequate approach for the calculation of thermal heat flux in the case of kitchen hob fires.